2015
DOI: 10.1177/2151458515588187
|View full text |Cite
|
Sign up to set email alerts
|

Change in Limb Length After Total Knee Arthroplasty

Abstract: The clinical outcome of total knee arthroplasty (TKA) remains suboptimal in some patients. One of the factors that might hinder improved functionality may be postoperative limb length discrepancy due to increase in limb length of the operative limb. The objective of this cross-sectional prospective study was to examine the extent to which limb length change occurs after TKA and to compare the change in limb length to the degree of valgus or varus joint position preoperatively. The role of body mass index and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…All TKAs were grouped three times discretely for analysis: grouping one consisted of varus and valgus groups, grouping two consisted of “customized” and “conventional” groups, and grouping three consisted of “severe varus,” “severe valgus,” and “moderate malalignment” groups. Values greater than 10° in either varus or valgus qualified into “severe varus” or “severe valgus,” respectively, with the third group of “moderate malalignment” to capture the remaining knees in accordance with previously published studies [ 2 , 8 ]. The mean limb lengthening and frequency of limb lengthening overall as well as the mean preoperative and postoperative alignment in each group were determined.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…All TKAs were grouped three times discretely for analysis: grouping one consisted of varus and valgus groups, grouping two consisted of “customized” and “conventional” groups, and grouping three consisted of “severe varus,” “severe valgus,” and “moderate malalignment” groups. Values greater than 10° in either varus or valgus qualified into “severe varus” or “severe valgus,” respectively, with the third group of “moderate malalignment” to capture the remaining knees in accordance with previously published studies [ 2 , 8 ]. The mean limb lengthening and frequency of limb lengthening overall as well as the mean preoperative and postoperative alignment in each group were determined.…”
Section: Methodsmentioning
confidence: 67%
“…This can occur after TKA due to limb lengthening of the operative leg [ 2 , 6 , 7 ]. Studies from 2012 and 2015 have shown that limb lengthening occurs frequently after TKA, though the extent of the lengthening is unclear [ 2 , 8 ]. Additionally, recent advances in total joint technology may permit greater control over limb lengthening to allow for more precise outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [ 13 ] reported the association between greater LLD with smaller BMI in their series of 466 patients at one-year follow-up[ 13 ]. All studies reported a greater increase in limb length following valgus deformity than varus[ 12 , 14 ]. The pooled analysis of two studies reporting the limb length variation following TKA observed limb lengthening of 7.06 mm in valgus deformity vs 4.42 in varus deformity ( P < 0.05)[ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported a greater increase in limb length following valgus deformity than varus[ 12 , 14 ]. The pooled analysis of two studies reporting the limb length variation following TKA observed limb lengthening of 7.06 mm in valgus deformity vs 4.42 in varus deformity ( P < 0.05)[ 12 , 14 ]. The LLD (MD -2.69 mm; 95%CI: -5.11, -0.27) was significantly less in varus knee compared to the valgus knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation